Implication of KDR Polymorphism rs2071559 on Therapeutic Outcomes and Safety of Postoperative Patients with Gastric Cancer Who Received S-1-Based Adjuvant Chemotherapy: A Real-World Exploratory Study - Meng L; Cao J; Kang L; Xu G; Yuan DW; Li K; Zhu K (Dove Medical Press, 2023)
Lei Meng,1,* Jun Cao,1,2,* Li Kang,3,* Gang Xu,1 Da-Wei Yuan,1 Kang Li,1 Kun Zhu1 1Department of Surgical Oncology, The First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, 710061, People's Republic of China; 2The Third Affiliated Hospital of Xi'an Medical University, Xi'an, 710068, People's Republic of China; 3Department of Thoracic Surgery, The First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, 710061, People's Republic of China*These authors contributed equally to this workCorrespondence: Kang Li; Kun Zhu, Department of Surgical Oncology, The First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, 710061, People's Republic of China, Tel +86 13087566643, Email healthlee@xjtu.edu.cn; dr.zhkun@mail.xjtu.edu.cnObjective: Regimens of S-1-based adjuvant chemotherapy are of great significance in attenuating recurrence risk in postoperative patients with gastric cancer (GC). Kinase insert-domain receptor (KDR) gene plays an essential role in tumor growth and metastasis. This study aimed to investigate the implication of KDR genotyping on the therapeutic outcomes of patients with gastric cancer (GC) who received S-1-based adjuvant chemotherapy.Methods: A total of 169 postoperative GC with pathological staging of II and III and no metastasis who received S-1-based adjuvant chemotherapy were included retrospectively. Peripheral blood specimens were collected and prepared for KDR genotyping and KDR mRNA expression. Correlation between KDR genotype status and prognosis was performed using Kaplan-Meier survival analysis, and multivariate analysis was ultimately adopted using Cox regression analysis.Results: Median disease-free survival (DFS) of the 169 patients with GC was 5.1 years [95% confidence interval (CI): 4.25- 5.95] and median overall survival (OS) was 6.7 years (95% CI: 5.44- 7.96). Rs2071559 was located at the upstream region, and the prevalence among 169 patients with GC was as follows: AA genotype in 104 cases (61.5%), AG genotype in 57 cases (33.7%), and GG genotype in 8 cases (4.7%), yielding a minor allele frequency of 0.22, which was consistent with Hardy-Weinberg equilibrium (P=0.958). Median DFS of patients with AA and AG/GG genotypes was 6.0 years and 4.0 years, respectively (P=0.002). Additionally, patients with the AA genotype had longer OS than those with the AG/GG genotype [median OS: not reached (NR) vs 5.5 years, P=0.011]. Additionally, KDR mRNA expression was significantly higher in patients with the AG/GG genotype than that in those with the AA genotype (P< 0.001).Conclusion: Rs2071559 in KDR gene might be a promising biomarker for evaluating the recurrence risk and OS of patients with GC who received S-1-based adjuvant chemotherapy. This conclusion should be confirmed in randomized clinical trials.Keywords: gastric cancer, S-1, KDR, polymorphism, prognosis, biomarker